Genetic Diversity of Leafy Liverwort Species (Jungermanniidae, Marchantiophyta) in Poland: Diversity of Leafy Liverwort Species with Various Reproductive Modes - Bączkiewicz, Alina (Biodiversity: Research and Conservation, 2013)
This monograph presents results of research on genetic diversity of 8 leafy liverwort species differing in reproductive mode. The frst 4 species in Poland are regarded as sterile and reproduce only vegetatively: Bazzania trilobata, Trichoc-olea tomentella, Lophozia hatcheri, and Mylia anomala. The next 4 are fertile, including the monoecious Lepidozia reptans and Calypogeia integristipula as well as the dioecious Mylia taylorii and Tritomaria quinquedentata. For each species, 9-10 populations were sampled. In total, 4744 gametophytes from 73 populations were examined by isozyme analysis. The level of their genetic diversity (total, HT, and within populations, HS) was high, higher than in thallose liverworts, but comparable to the genetic diversity of mosses or even some species of vascular plants. Thus the traditional opinion that the entire group of liverworts has a much lower level of genetic diversity than mosses is erroneous, as it holds true only for thallose liverworts (Metzgeriidae and Marchantiopsida). My results indicate that the effect of reproductive mode on genetic diversity in leafy liverworts is lower than in vascular plants. Sterile and fertile species of liverworts exhibited similar levels of genetic diversity. Moreover, both groups included species that had both high and low levels of HT and HS. In fertile species, monoecious and dioecious species also did not differ signifcantly in genetic diversity, but dioecious liverworts had slightly higher total diversity (HT) than monoecious species. In most of the studied leafy liverworts, the share of genetic diversity within populations in the total genetic diversity of species is greater than between populations. The percentage share of variation among populations (ΦPT) in the total genetic variation was correlated with the total genetic diversity of the species (HT). In species with high HT, differences between populations tended to be rather small. By contrast, in species with lower HT, the percentage share of differentiation among populations in the total diversity of species was much higher. My results confrm theory, based on studies by Kimura, that the main causes of genetic diversity of bryophytes are neutral somatic mutations developing in various vegetative parts of plants. The separation of branches or other plant sections with somatic mutations, followed by the growth of new shoots, can increase the level of genetic diversity. The high level of genetic diversity in sterile liverworts indicates that vegetative reproduction has a greater infuence on the level of genetic diversity than recombination. My results suggest also that mutation rates are similar in closely related species, but species with a wider ecological range exhibit higher genetic diversity because the variability of habitats can infuence the rate and type of somatic mutations. Accordingly, species inhabiting more diverse environments may be more genetically diverse. Patches of the studied species generally consisted of several genotypes (MLGs). Two types of distribution of genotypes in patches were noticed. Patches of species with low total diversity (HT), were often dominated by 1-2 genotypes, which constituted the major part of a patch. In patches of species with higher HT, there was no tendency to form patches with predomination of a single genotype. Different genotypes constituted similar proportions of a patch. In all the studied leafy liverwort species there was a high degree of repeatability of the same genotypes (MLGs) in plants from various patches within the same population or in various populations. Probably the main cause of this is the independent repeatability of the same mutations in different specimens.